Human–Computer Interaction Based on Scan-to-BIM Models, Digital Photogrammetry, Visual Programming Language and eXtended Reality (XR) - Banfi, Fabrizio; Previtali, Mattia (Applied sciences, 2021)
In recent years, the advent of the latest-generation technologies and methods have made it possible to survey, digitise and represent complex scenarios such as archaeological sites and historic buildings. Thanks to computer languages based on Visual Programming Language (VPL) and advanced real-time 3D creation platform, this study shows the results obtained in eXtended Reality (XR) oriented to archaeological sites and heritage buildings. In particular, the scan-to-BIM process, digital photogrammetry (terrestrial and aerial) were oriented towards a digitisation process able to tell and share tangible and intangible values through the latest generation techniques, methods and devices. The paradigm of the geometric complexity of the built heritage and new levels of interactivity between users and digital worlds were investigated and developed to favour the transmissibility of information at different levels of virtual experience and digital sharing with the aim to archive, tell and implement historical and cultural baggage that over the years risks being lost and not told to future generations.